The Impact of Environmental Stress on Plant Cell Structure and Function - Astria, Astria; Yofran, Yuliani Putri; Ngama, Yulita Erlina; Bhaghi, Emaliano Jonsimus Lea; Wae, Veronika P. Sinta Mbia (Jurnal Biologi Tropis, 2025)
Environmental stress is an external factor that affects the strength and function of plant cells, such as salt levels, extreme temperatures, heavy metals, and radiation. This can cause significant changes at the molecular level, including cell structure and chemical processes within plants. This article is a systematic summary of 30 scientific studies published in the last ten years, aiming to identify common patterns in how plant cells respond to non-living stressors. Studies have shown that environmental stressors can lead to the accumulation of free radicals (ROS). This can damage membranes, cause lipid oxidation, damage chloroplasts, and disrupt the activity of enzymes essential for photosynthesis and respiration. At the molecular level, adaptive responses occur by activating hormone signaling pathways, particularly abscisic acid (ABA) and ethylene. This also involves increased expression of genes related to water regulation and protection from oxidation, as well as activation of autophagy, a mechanism that destroys damaged cell parts. Changes in cellular components such as the vacuole, mitochondria, and cell wall indicate how cells work to maintain salt balance and basic body processes. This summary of various studies shows that environmental stress can cause complex problems, such as disruptions in metabolic processes, instability of internal organs, and changes in gene expression. Therefore, understanding how plant cells work and their structure is crucial for developing plant varieties that are resilient to climate change stress.